BETWEEN CONTEXTUALIZATION AND DISTORTION: INTERPRETATION OF QUR’ANIC VERSES ON NATIONALISM IN DETIK.COM AND NU ONLINE - Lufaefi, Lufaefi; Fahriana, Lukita (Sekolah Tinggi Agama Islam Sadra, 2025)
The development of digital media has significantly transformed the patterns of Qur’anic interpretation, including on the issue of nationalism in Islam. This study analyzes how verses related to nationalism are interpreted by two online media platforms: Detik.com and NU Online. Using a qualitative method with content analysis and Critical Discourse Analysis approaches, Detik.com interprets Q.S. Al-Isrā’ [17]: 70 as a foundation for freedom and human dignity, although academic tafsir traditionally views this verse as referring to the general honor bestowed upon humankind. The platform also uses Q.S. Al-Mumtaḥanah [60]: 8 to equate love for the homeland with defending religion, despite the verse’s original context focusing more on social relations and tolerance. Meanwhile, NU Online references Q.S. Al-Qaṣaṣ [28]: 85 as theological legitimacy for love of one's homeland, although it primarily refers to Allah’s promise to the Prophet Muhammad regarding his return to Mecca. Likewise, Q.S. An-Nisā’ [4]: 66 is interpreted as evidence of the significance of one’s birthplace, even though the verse contextually concerns the command to emigrate as a test of faith. The findings reveal that while these interpretations aim to contextualize nationalism within Islam, there is a tendency toward distortion due to selective verse usage and deviations from established academic tafsir methodology. It is crucial to apply sound and objective interpretive methods that go beyond pragmatic interests and remain academically accountable. This ensures that interpretations of nationalism-related verses in Islam reflect the Qur’an’s teachings in a comprehensive, logical manner, avoiding narrow ideological biases that risk diminishing the depth of the sacred text.